The Isolation and Electrochemical Studies of Flavanoids from Galenia africana and Elytropapus rhinocerotis from the North Western Cape - Maiko, Khumo Gwendoline (University of the Western Cape, 2014)
Magister Scientiae - MSc === In this study two medicinal plant species, namely Galenia africana and Elytropapus rhinocerotis, the former belonging to the family Aizoceae and the latter belonging to the family Asteraceae, have been investigated and different compounds isolated and characterized. Both species are important plants used in traditional medicine in Africa and particularly in South Africa. Flavanoids are secondary metabolites found in plants. They have a protective function against UV radiation and have a defence against invading illnesses due to their important antioxidant activity. Much of the food we eat and some beverages we drink contain flavonoids. The aim of this study was to investigate the electrochemistry of flavanoids isolated from these species. === South Africa